Preparation and application of monatomic metal doped hydrophobic molybdenum disulfide catalyst

By preparing a single-atom metal-doped hydrophobic MoS2 catalyst, the existing catalysts have been solved in terms of stability, cost and synthesis complexity, and the efficiency, stability and economicality of the hydrodeoxygenation reaction of biomass oil are achieved.

CN119702011AActive Publication Date: 2025-03-28FUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510026560.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing hydrodeoxygenation catalysts have problems in terms of stability, cost and synthesis complexity, making it difficult to achieve efficient, stable and inexpensive hydrodeoxygenation reactions of biomass oils.

Method used

A hydrophobic MoS2 catalyst doped with a single atomic metal is prepared by in-situ vulcanization reaction of molybdenum-based ionic liquid, sulfur powder and dehydronaphthalene, combined with the doping reaction of metal ionic liquid, a highly efficient, stable and hydrophobic catalyst is prepared.

Benefits of technology

The efficiency and stability of the hydrodeoxygenation reaction of biomass oil is achieved, energy consumption and cost are reduced, high purity and high yield of the product are improved, and the economic value of biomass oil is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702011A_ABST
    Figure CN119702011A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a monatomic metal doped hydrophobic MoS2 catalyst. The preparation method comprises the following steps: by taking molybdenum-based ionic liquid as a precursor, preparing a molybdenum sulfide carrier through in-situ vulcanization, doping metal on the surface of the molybdenum sulfide carrier by utilizing a solvothermal technology, and performing reduction treatment through a tubular furnace, thereby finally obtaining the target monatomic metal doped hydrophobic catalyst. The catalyst shows excellent activity and stability in a hydrodeoxygenation reaction of biomass oil. The invention provides an innovative preparation strategy of the monatomic metal hydrophobic catalyst with high cost effectiveness, opens up a new direction for industrial production and wide application of the catalyst, and is beneficial to promoting the development of a green chemical process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomass oil hydrodeoxygenation catalysis, and specifically relates to a preparation method and application of a single-atom metal-doped hydrophobic MoS2 catalyst. Background Art

[0002] With the rapid development of the global industrial economy and the continuous advancement of modernization construction, fossil energy such as oil, natural gas, and coal are becoming increasingly depleted, and the ecological environment is deteriorating. In particular, the global greenhouse effect and acid rain caused by exhaust gases emitted after the combustion of fossil fuels have seriously threatened the sustainable development of human society and national energy security. The development of green and environmentally friendly renewable energy has attracted widespread attention worldwide.

[0003] Among many new energy sources, biomass oil can be regarded as an ideal new energy source that can replace fossil fuels. Biomass has the characteristics of abundant resources, renewable, and wide distribution. It has been widely studied and developed and has great application prospects. However, the unrefined biomass oil has a very high oxygen content, which will lead to the deterioration of bio-oil performance, such as low calorific value, strong corrosiveness, and poor stability. Hydrodeoxygenation (HDO) is one of the effective means of refining biomass oil. It can convert oxygen-containing compounds into value-added chemicals and sustainable production fuels, and has attracted widespread attention in the scientific community. To this end, researchers have done a lot of research on catalytic hydrodeoxygenation of biomass oil. The core issue in the catalytic conversion technology of biomass oil is the design and construction of efficient, stable and inexpensive hydrodeoxygenation catalysts.

[0004] Commonly used hydrodeoxygenation catalysts, such as precious metal catalysts, often lead to excessive hydrogenation of aromatic rings to generate by-products, and the reaction conditions are harsh, requiring high hydrogen pressure and high temperature, resulting in high hydrogen consumption, large energy loss and other problems. In addition, precious metals are expensive, so such catalysts are difficult to apply on a large scale; in addition, sulfurized catalysts such as Ni, Co, Mo, W and their combinations have high hydrodeoxygenation performance, but poor reaction stability, and problems such as sulfur loss and carbon deposition will occur. Therefore, it is of great significance to develop an efficient, stable and inexpensive biomass oil hydrodeoxygenation catalyst. Summary of the invention

[0005] In order to overcome the problems of stability, cost and synthesis complexity of existing hydrodeoxygenation catalysts, the present invention provides an innovative preparation method and application strategy of a single-atom metal-doped hydrophobic MoS2 catalyst. The preparation method described in the present invention is not only simple in process and convenient for large-scale production, but also the prepared catalyst exhibits excellent activity and stability in the hydrodeoxygenation reaction of biomass oil, providing a reliable catalytic solution for the efficient conversion of biomass oil.

[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst comprises the following steps: 1) In-situ sulfurization reaction of molybdenum-based ionic liquid, sulfur powder and decahydronaphthalene is carried out in a reactor, and after cooling to room temperature, the reaction is centrifuged and washed, and vacuum dried to constant weight to obtain a MoS2 carrier; 2) The metal ion liquid, decahydronaphthalene and the MoS2 carrier prepared in step 1) are subjected to a doping reaction in a reactor. After cooling to room temperature, the mixture is centrifugally washed, vacuum dried to constant weight, and then reduced in a tubular furnace to obtain the single-atom metal-doped hydrophobic MoS2 catalyst.

[0007] Furthermore, the molybdenum-based ionic liquid in step 1) is [N 8881 ]2MoO4, the amount used is calculated based on the Mo content in the system being 1000 ppm~8000 ppm.

[0008] Furthermore, the amount of sulfur powder used in step 1) is converted according to the S / Mo atomic ratio of 1 to 20 in the system.

[0009] Furthermore, the temperature of the in-situ sulfidation reaction in step 1) is 180-360°C, the time is 0-36 h, and the hydrogen pressure is 0-8 MPa.

[0010] Furthermore, the metal ionic liquid in step 2) is [N 8881 ]2CoCl4, [N 8881 ]FeCl4, [N 8881 ]2NiCl4, [N 8881 ]2CuCl4, [N 8881 ]2ZnCl4, [N 8881 ]One or more of 2WO4.

[0011] Furthermore, the amount of the metal ion liquid in step 2) is converted according to a molar ratio of 0 to 3 between the metal ion liquid and the metal atoms in the MoS2 carrier.

[0012] Furthermore, the doping reaction in step 2) is carried out under normal pressure N2 atmosphere, the reaction temperature is 250~450℃, and the reaction time is 0~36h.

[0013] Furthermore, the reduction in step 2) is carried out in a mixed gas atmosphere of 10% H2 / 90% Ar, the reaction temperature is 150-800°C, and the reaction time is 1-10 h.

[0014] Furthermore, the centrifugal speed in steps 1) and 2) is 5000-120000 r / min.

[0015] Furthermore, the vacuum drying in steps 1) and 2) is carried out at a temperature of 80 to 150°C and a time of 6 to 24 hours.

[0016] The single-atom metal-doped hydrophobic MoS2 catalyst prepared by the above method can be used for the hydrodeoxygenation or hydroreduction reaction of one or more biomass oils including lignin pyrolysis oil, biomass pyrolysis oil, biomass-based oxygen-containing compounds, bio-oils, etc.

[0017] Furthermore, in the reaction, the mass ratio of the single-atom metal-doped hydrophobic MoS2 catalyst to the biomass oil used is 1~20%, the reaction hydrogen pressure is 0~10 MPa, the reaction temperature is 30~400°C, the reaction time is 0~36 h, and the hydrogen-to-oil ratio is 0~2000.

[0018] The technical solution of the present invention has the following advantages: 1) The preparation process of the single-atom metal-doped hydrophobic MoS2 catalyst proposed in the present invention uses metal ion liquid as a precursor, which exhibits better uniform distribution characteristics than traditional metal sources, thereby achieving highly uniform dispersion of metals and helping to reduce impurity generation. Based on the advantages of metal ion liquid in structural controllability, it can effectively promote strong interactions between metal ions and carriers, and easily form a low-coordination catalytic environment, thereby significantly improving the stability of the catalyst, which is crucial for improving catalytic efficiency. In addition, metal ion liquid, as an oil-soluble precursor, can make the final prepared catalyst have excellent hydrophobicity. Hydrophobic catalysts can effectively repel water molecules, reduce competitive adsorption of water on the catalyst surface, and thus enhance the stability and activity of the catalyst. At the same time, this catalyst can also promote the adsorption of organic components in biomass oil on its surface, optimize the mass transfer process of reactants, while reducing energy consumption and costs, achieving high purity and high yield of products, thereby enhancing the economic value of biomass oil. Therefore, the present invention successfully solves the key problems of the existing single-atom metal-doped MoS2 catalyst in terms of insufficient stability and complex synthesis process, and provides a catalyst design scheme with high efficiency, high stability and significant cost-effectiveness for the research and industry. This breakthrough not only promotes the research progress of single-atom metal-doped hydrophobic MoS2 catalysts, but also provides a new technical approach for the hydrodeoxygenation process of biomass oil, which is expected to have a far-reaching impact in the fields of renewable energy conversion and fine chemicals.

[0019] 2) The present invention provides an innovative preparation process for a single-atom metal-doped hydrophobic MoS2 catalyst, in which decalin is selected as a reaction solvent during the in-situ synthesis of the single-atom catalyst. As an efficient organic solvent, decalin provides an ideal medium environment for the interaction between the metal ion liquid and the carrier, which promotes the effective combination between the two. In addition, the hydrophobic nature of decalin significantly enhances the hydrophobicity of the single-atom catalyst, which is particularly beneficial for the biooil hydrodeoxygenation (HDO) reaction. This hydrophobicity helps to reduce the competitive adsorption of water on the catalyst surface, thereby reducing the negative impact of water on the catalytic activity. Therefore, the preparation process of the present invention not only ensures the high efficiency of the catalyst, but also improves its stability and selectivity in the biooil HDO reaction.

[0020] 3) The single-atom metal-doped MoS2 catalyst prepared by the present invention can achieve deep deoxygenation of different biomass oil products. Specifically, the single-atom metal-doped hydrophobic MoS2 catalyst prepared by the present invention can selectively break the carbon-oxygen bonds of alcohol hydroxyl groups, phenolic hydroxyl groups, fatty acids, fatty acid esters and glycerides, so that the deoxygenation degree of biomass oil reaches more than 92% and the target product selectivity reaches more than 90%. In addition, the structure of the single-atom metal-doped hydrophobic MoS2 catalyst is highly designable and can be widely used in the hydrodeoxygenation process of different biomass oils. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD pattern of the catalyst Co / MoS2 prepared in Example 2.

[0022] Figure 2 HAADF-STEM image of the catalyst Co / MoS2 prepared in Example 2 and its corresponding EDS element distribution map.

[0023] Figure 3 This is the air-water contact angle diagram of the catalyst Co / MoS2 prepared in Example 2. DETAILED DESCRIPTION

[0024] A method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst comprises the following steps: 1) Weigh a certain amount of molybdenum-based ionic liquid [N 8881 ]2MoO4, sulfur powder and decahydronaphthalene are placed in a high pressure reactor for in-situ sulfurization reaction at 180-360 ℃ and hydrogen pressure of 0-8 MPa for 0-36 h, and after cooling to room temperature, they are centrifuged and washed at 5000-120000 r / min, and vacuum dried at 80-150 ℃ for 6-24 h to constant weight to obtain a MoS2 carrier; 2) Weigh a certain amount of metal ionic liquid, decahydronaphthalene and the MoS2 carrier prepared in step 1) and add them into a high-pressure reactor. Under normal pressure N2 atmosphere, react at 250-450 °C for 0-36 h. After cooling to room temperature, centrifuge and wash at 5000-120000 r / min, and vacuum dry at 80-150 °C for 6-24 h to constant weight. Then place the sample in a tubular furnace and reduce it at 150-800 °C for 1-10 h in a mixed gas atmosphere of 10% H2 / 90% Ar to obtain a single-atom metal-doped hydrophobic MoS2 catalyst.

[0025] Wherein, the amount of molybdenum-based ionic liquid used in step 1) is converted according to the Mo content in the system being 1000 ppm to 8000 ppm; the amount of sulfur powder used is converted according to the S / Mo atomic ratio in the system being 1 to 20.

[0026] The metal ionic liquid in step 2) is [N 8881 ]2CoCl4, [N 8881 ]FeCl4, [N 8881 ]2NiCl4, [N 8881 ]2CuCl4, [N 8881 ]2ZnCl4, [N 8881 ]2WO4. The amount thereof is calculated according to the molar ratio of the molar ratio of the molar ratio to the metal atoms in the MoS2 carrier being 0-3.

[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention will be described in detail below through specific embodiments.

[0029] Embodiment 1: A single-atom metal-doped hydrophobic MoS2 catalyst Fe / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed. High-purity hydrogen was introduced to replace the air in the reactor and the pressure was increased to 4 MPa. The temperature was then raised to 280 °C at a rate of 5 °C / min and the reaction was continued for 24 h. After the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to obtain a constant weight to obtain a MoS2 carrier. (2) Weigh 0.2617 g of [N 8881 ]FeCl4, 15 g of decahydronaphthalene and 0.1056 g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining a normal pressure N2 atmosphere. The temperature was then raised to 320 °C at a rate of 5 °C / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged and washed at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, a mixed gas of 10% H2 / 90% Ar was introduced, and the target catalyst Fe / MoS2 was obtained, wherein the Fe / Mo molar ratio was 0.7.

[0030] The prepared catalyst Fe / MoS2 was used for the selective deoxygenation of p-methylphenol. Specifically, 0.0068 g of Fe / MoS2, 0.08 g of p-methylphenol and 2.2 g of dodecane were weighed and added to a 10 mL high-pressure reactor, which was sealed. High-purity H2 was introduced to replace the air in the reactor and pressurized to 4 MPa. Then the temperature was raised to 300 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 6 h. After the reactor was cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol. The qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of p-methylphenol treated with Fe / MoS2 was 100%, and the selectivity of the main product toluene was 96.5%.

[0031] Embodiment 2: A single-atom metal-doped hydrophobic MoS2 catalyst Co / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.1858 g of [N 8881]2CoCl4, 15 g decahydronaphthalene and 0.1056 g prepared MoS2 carrier were added into a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining the normal pressure N2 atmosphere. Then, the temperature was raised to 320 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction liquid was placed in a centrifuge and centrifuged and washed at 5000r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 ℃ for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, and a mixed gas of 10% H2 / 90% Ar was introduced and reduced at 350 ℃ for 2 h to obtain the target catalyst Co / MoS2, in which the Co / Mo molar ratio was 0.3.

[0032] The prepared catalyst Co / MoS2 was used for the selective deoxygenation of nitrobenzene. Specifically, 0.008 g of Co / MoS2, 0.06 g of nitrobenzene and 1.6 g of methanol were weighed and added to a 10 mL high-pressure reactor, which was sealed. High-purity H2 was introduced to replace the air in the reactor and pressurized to 0.5 MPa. Then the temperature was raised to 40 °C at a rate of 5 °C / min and the reaction was continued for 5 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol. The qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of nitrobenzene treated with Co / MoS2 was 100%, and the selectivity of the main product aniline was 100%.

[0033] Embodiment 3: A single-atom metal-doped hydrophobic MoS2 catalyst Ni / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.1858 g of [N 8881]2NiCl4, 15 g of decahydronaphthalene and 0.1056 g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining a normal pressure N2 atmosphere. The temperature was then raised to 320 °C at a rate of 5 °C / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, a mixed gas of 10% H2 / 90% Ar was introduced, and the target catalyst Ni / MoS2 was obtained, wherein the Ni / Mo molar ratio was 0.3.

[0034] The prepared catalyst Ni / MoS2 was used for the selective deoxygenation of methyl palmitate. Specifically, 0.03 g of Ni / MoS2, 0.5 g of methyl palmitate and 1.8 g of n-heptane were weighed and added to a 10 mL high-pressure reactor, which was sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 5 MPa, and then the temperature was raised to 280 ℃ at a rate of 5 ℃ / min and reacted for 8 h. After the reactor was cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in ethyl acetate, and qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of methyl palmitate treated with Ni / MoS2 was 99.1%, and the selectivity of the product alkane was 95.2%.

[0035] Embodiment 4: A single-atom metal-doped hydrophobic MoS2 catalyst Zn / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g of decahydronaphthalene and 0.5 g of sulfur powder were added into a 100 mL high-pressure reactor, which was sealed. High-purity hydrogen was introduced to replace the air in the reactor and the pressure was increased to 4 MPa. The temperature was then raised to 280 °C at a rate of 5 °C / min and the reaction was continued for 24 h. After the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to obtain a constant weight to obtain a MoS2 carrier. (2) Weigh 0.3118 g of [N 8881]2ZnCl4, 15 g decahydronaphthalene and 0.1056 g prepared MoS2 carrier were added into a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while retaining the normal pressure N2 atmosphere. Then, the temperature was raised to 320 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 5 h. After the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 ℃ for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, and a mixed gas of 10% H2 / 90% Ar was introduced and reduced at 300 ℃ for 4 h to obtain the target catalyst Zn / MoS2, wherein the Zn / Mo molar ratio was 0.5.

[0036] The prepared catalyst Zn / MoS2 was used for the selective deoxygenation of sunflower oil. Specifically, 0.1 g of Zn / MoS2 and 2.4 g of sunflower oil were weighed and added to a 10 mL high-pressure reactor, which was sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 6 MPa. Then, the temperature was raised to 350 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 10 h. After the reactor was cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol, and qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of sunflower oil treated with Zn / MoS2 was 92.8%, and the selectivity of the main product alkane was 95.1%.

[0037] Embodiment 5: A single-atom metal co-doped hydrophobic MoS2 catalyst Co-Fe / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.1239 g of [N 8881 ]2CoCl4, 0.1869 g of [N 8881]2FeCl4, 15 g of decahydronaphthalene and 0.1056 g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining the normal pressure N2 atmosphere. The temperature was raised to 320 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 ℃ for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, a mixed gas of 10% H2 / 90% Ar was introduced, and the target catalyst Co-Fe / MoS2 was obtained, wherein the Co / Fe molar ratio was 0.4 and the (Co+Fe) / Mo molar ratio was 0.7.

[0038] The prepared catalyst Co-Fe / MoS2 was used for the selective deoxygenation of p-methylphenol. Specifically, 0.0068g of Co-Ni / MoS2, 0.08g of p-methylphenol and 2.2g of dodecane were weighed and added into a 10 mL high-pressure reactor, which was sealed. High-purity H2 was introduced to replace the air in the reactor and pressurized to 4 MPa. Then the temperature was raised to 180 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 10 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol and qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry. The results showed that the deoxygenation degree of p-methylphenol treated with Co-Fe / MoS2 was 100%, and the selectivity of the main product toluene was 99.8%.

[0039] Embodiment 6: A single-atom metal co-doped hydrophobic MoS2 catalyst Co-Zn / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.1858 g of [N 8881 ]2CoCl4, 0.0624 g of [N 8881]2ZnCl4, 15g of decahydronaphthalene and 0.1056g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining the normal pressure N2 atmosphere. The temperature was raised to 320°C at a rate of 5°C / min and the reaction was carried out for 5 hours. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80°C for 12 hours to make it constant weight. The dried sample was then placed in a tubular furnace, a mixed gas of 10% H2 / 90% Ar was introduced, and the target catalyst Co-Zn / MoS2 was obtained, wherein the Zn / Co molar ratio was 0.3 and the (Co+Zn) / Mo molar ratio was 0.4.

[0040] The prepared catalyst Co-Zn / MoS2 was used for the selective deoxygenation of methyl palmitate. Specifically, 0.01 g of Co-Zn / MoS2, 0.03 g of methyl palmitate and 3.0 g of decane were weighed and added into a 10 mL high-pressure reactor, which was sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 240 ℃ at a rate of 5 ℃ / min and reacted for 4 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in ethyl acetate, and qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of methyl palmitate treated with Co-Zn / MoS2 was 100%, and the selectivity of the main product alkane was 95.6%.

[0041] Embodiment 7: A single-atom metal co-doped hydrophobic MoS2 catalyst Fe-Ni / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.0374 g of [N 8881 ]FeCl4, 0.1238 g [N 8881]2NiCl4, 15 g of decahydronaphthalene and 0.1056 g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining the normal pressure N2 atmosphere. The temperature was raised to 320 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 ℃ for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, and a mixed gas of 10% H2 / 90% Ar was introduced, and reduced at 450 ℃ for 2 h to obtain the target catalyst Fe-Ni / MoS2, in which the Ni / Fe molar ratio was 0.5 and the (Fe+Ni) / Mo molar ratio was 0.3.

[0042] The prepared catalyst Fe-Ni / MoS2 was used for the selective deoxygenation of lignin pyrolysis oil. Specifically, 0.03g of Fe-Ni / MoS2, 0.08g of lignin pyrolysis oil and 2.2g of dodecane were weighed and added to a 10 mL high-pressure reactor, which was sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 200 ℃ at a rate of 5 ℃ / min and reacted for 8h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol, and qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of lignin pyrolysis oil treated with Fe-Ni / MoS2 was 100%.

[0043] Embodiment 8: A single-atom metal co-doped hydrophobic MoS2 catalyst Cu-Zn / MoS2 is prepared, and the steps are as follows: (1) Weigh 1.9205 g of ionic liquid [N 8881 ]2MoO4, 30 g decahydronaphthalene and 0.3405 g sulfur powder were added into a 100 mL high-pressure reactor, which was sealed, and high-purity hydrogen was introduced to replace the air in the reactor and pressurized to 4 MPa, and then the temperature was raised to 280 °C at a rate of 5 °C / min and reacted for 24 h; after the reactor cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 °C for 12 h to make it constant weight to obtain a MoS2 carrier; (2) Weigh 0.0622 g of [N 8881 ]2CuCl4, 0.0624 g [N 8881]2ZnCl4, 15 g of decahydronaphthalene and 0.1056 g of the prepared MoS2 carrier were added to a 25 mL high-pressure reactor, sealed, and high-purity N2 was introduced to replace the air in the reactor while maintaining the normal pressure N2 atmosphere. The temperature was raised to 320 ℃ at a rate of 5 ℃ / min and the reaction was carried out for 5 h. After the reactor was cooled to room temperature, the reaction solution was placed in a centrifuge and centrifuged at 5000 r / min to obtain a solid sample, which was then placed in a vacuum drying oven and dried at 80 ℃ for 12 h to make it constant weight. The dried sample was then placed in a tubular furnace, and a mixed gas of 10% H2 / 90% Ar was introduced, and reduced at 300 ℃ for 3 h to obtain the target catalyst Cu-Zn / MoS2, in which the Cu / Zn molar ratio was 1 and the (Cu+Zn) / Mo molar ratio was 0.2.

[0044] The prepared catalyst Cu-Zn / MoS2 was used for the selective deoxygenation of waste oil. Specifically, 0.05 g of Cu-Zn / MoS2, 0.08 g of waste oil and 2.2 g of dodecane were weighed and added to a 10 mL high-pressure reactor, which was sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 5 MPa, and then the temperature was raised to 280 ℃ at a rate of 5 ℃ / min and reacted for 12 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol, and qualitative and quantitative analysis was performed using a gas chromatography-mass spectrometer. The results showed that the deoxygenation degree of the waste oil treated with Cu-Zn / MoS2 was 97.6%, and the selectivity of alkanes was 92.3%.

[0045] Comparative Example 1: 0.1858 g of [N 8881 ]2CoCl4 was replaced with 0.0351 g of cobalt acetate, and the remaining operations were the same as in Example 2 to finally obtain Co 1 / MoS2 catalyst, wherein the Co / Mo molar ratio is 0.3.

[0046] The prepared catalyst Co 1 / MoS2 is used for the selective deoxygenation of nitrobenzene, specifically, 0.008 g of Co 1 / MoS2, 0.06 g nitrobenzene and 1.6 g methanol were added to a 10 mL high-pressure reactor, sealed, and high-purity H2 was introduced to replace the air in the reactor, and the pressure was increased to 0.5 MPa, and then the temperature was raised to 40 ℃ at a rate of 5 ℃ / min and the reaction was continued for 5 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol, and qualitative and quantitative analysis was performed using gas chromatography-mass spectrometry. The results showed that after Co 1 The deoxygenation degree of nitrobenzene treated with / MoS2 is 19%, and the selectivity of the main product aniline is 97%.

[0047] Comparative Example 2: 0.1858 g of [N 8881 ]2CoCl4 was replaced with 0.0257 g of CoCl2, and the remaining operations were the same as in Example 2 to finally obtain Co 2 / MoS2 catalyst, wherein the Co / Mo molar ratio is 0.3.

[0048] The prepared catalyst Co 2 / MoS2 is used for the selective deoxygenation of nitrobenzene. Specifically, 0.008 g of Co / MoS2, 0.06 g of nitrobenzene and 1.6 g of methanol are weighed and added to a 10 mL high-pressure reactor, which is sealed and filled with high-purity H2 to replace the air in the reactor. The reactor is pressurized to 0.5 MPa, and then the temperature is raised to 40 °C at a rate of 5 °C / min and the reaction is carried out for 5 h. After the reactor cools to room temperature, the reaction liquid is filtered and separated, and the filter residue is fully dissolved in methanol, and qualitative and quantitative analysis is performed using a gas chromatography-mass spectrometer. The results show that after Co 2 The deoxygenation degree of nitrobenzene treated with / MoS2 is 8%, and the selectivity of the main product aniline is 100%.

[0049] Comparative Example 3: The reaction solvent decalin used in Example 2 was replaced with an equal volume of dodecane, and the remaining operations were the same as in Example 2 to finally obtain Co 3 / MoS2 catalyst.

[0050] The prepared catalyst Co 3 / MoS2 is used for the selective deoxygenation of nitrobenzene, specifically, 0.008 g of Co 3 / MoS2, 0.06 g nitrobenzene and 1.6 g methanol were added to a 10 mL high-pressure reactor, sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 0.5 MPa, then the temperature was raised to 40 °C at a rate of 5 °C / min and the reaction was continued for 5 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol and qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry. The results showed that the Co 3 The deoxygenation degree of nitrobenzene treated with / MoS2 is 78%, and the selectivity of the main product aniline is 85%.

[0051] Comparative Example 4: The reaction solvent decalin used in Example 2 was replaced with an equal volume of cyclohexane, and the remaining operations were the same as in Example 2 to finally obtain Co 4 / MoS2 catalyst.

[0052] The prepared catalyst Co 4 / MoS2 is used for the selective deoxygenation of nitrobenzene, specifically, 0.008 g of Co 3 / MoS2, 0.06 g nitrobenzene and 1.6 g methanol were added to a 10 mL high-pressure reactor, sealed, and high-purity H2 was introduced to replace the air in the reactor and pressurized to 0.5 MPa, then the temperature was raised to 40 °C at a rate of 5 °C / min and the reaction was continued for 5 h. After the reactor cooled to room temperature, the reaction liquid was filtered and separated, and the filter residue was fully dissolved in methanol and qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry. The results showed that the Co 4 The deoxygenation degree of nitrobenzene treated with / MoS2 is 90%, and the selectivity of the main product aniline is 95%.

[0053] The above results show that the catalyst prepared by the method of the present invention has a high biomass oil hydrodeoxygenation activity, can realize the biomass oil hydrodeoxygenation process under mild conditions, the deoxygenation rate is close to 100%, and the yield of the main product is as high as more than 90%, among which the effect of Example 2 is better.

[0054] The Co-MoS2 catalyst prepared in Example 2 was subjected to XRD analysis, and the results are as follows: Figure 1 shown. Figure 1 It shows that the diffraction peaks at 13.2°, 33.5°, and 58.9° can be attributed to the (002), (101), and (110) crystal planes of MoS2, respectively (JCPDS No. 37-1492), while no characteristic diffraction peaks related to the doped metal Co were found, indicating that the metal dispersion is relatively uniform.

[0055] Through in-depth analysis of Comparative Examples 1 and 2 and Example 2, it can be found that the catalyst prepared using metal ion liquid as a precursor has excellent performance, especially in terms of conversion rate and selectivity. This is because the metal ion liquid not only promotes a strong interaction between the metal ions and the carrier, but also promotes the uniform dispersion of the metal ions on the surface of the carrier, which effectively reduces the generation of impurities. In addition, this uniform dispersion provides favorable conditions for the formation of low-coordinated single-atom catalyst structures, which is crucial for improving catalyst activity. HAADF-STEM image of the Co / MoS2 catalyst prepared according to Example 2 and its corresponding EDS element distribution map ( Figure 2 ) It can be clearly observed that the Co element is uniformly dispersed on the MoS2 carrier in the form of single atoms. This result shows that during the in-situ synthesis process using metal ionic liquid as a precursor, Co atoms are successfully anchored on the surface of MoS2 in the form of single atoms without forming larger agglomerates or nanoparticles. This single-atom dispersion state is an ideal form pursued in catalyst design because it can maximize the catalytic activity of metal atoms while reducing the amount of metal used and improving catalytic efficiency and selectivity.

[0056] The results of Comparative Examples 3, 4 and Example 2 show that in the application of hydrodeoxygenation, the catalyst prepared using decalin as a solvent exhibits better performance. This advantage can be attributed in part to the high solubility of metal ionic liquids as oil-soluble precursors in decalin, which helps to ensure uniform dispersion of the precursor and uniform formation of subsequent catalysts. In addition, the hydrophobic nature of decalin is particularly advantageous in the preparation of hydrophobic catalysts, as it helps to form a hydrophobic layer on the catalyst surface, which is very important for catalytic reactions that require the repulsion of moisture, such as the hydrodeoxygenation of biomass oil (the presence of moisture may interfere with the catalytic reaction and reduce the activity and selectivity of the catalyst, while the hydrophobic surface can effectively reduce such interference). In order to verify the hydrophobicity of the catalyst, the air-water contact angle of the Co / MoS2 catalyst prepared in Example 2 was measured, and the results are as follows: Figure 3 As shown in the figure, the air-water contact angle of the catalyst reaches 108.9°, proving its excellent hydrophobicity. This result not only shows that the method of the present invention can successfully prepare a highly hydrophobic catalyst, but also provides an efficient catalytic solution for the hydrodeoxygenation reaction of biomass oil.

[0057] Any matters not described in the present invention are applicable to the prior art.

[0058] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst, characterized in that: The following steps are involved: 1) In-situ sulfurization reaction of molybdenum-based ionic liquid, sulfur powder and decahydronaphthalene is carried out in a reactor, and after cooling to room temperature, the reaction is centrifuged and washed, and vacuum dried to constant weight to obtain a MoS2 carrier; 2) The metal ion liquid, decahydronaphthalene and the MoS2 carrier prepared in step 1) are subjected to a doping reaction in a reactor. After cooling to room temperature, the mixture is centrifugally washed, vacuum dried to constant weight, and then reduced in a tubular furnace to obtain the single-atom metal-doped hydrophobic MoS2 catalyst.

2. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The molybdenum-based ionic liquid in step 1) is [N 8881 ]2MoO4; its dosage is calculated based on the Mo content in the system being 1000 ppm~8000 ppm.

3. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The amount of sulfur powder used in step 1) is converted according to the S / Mo atomic ratio of 1 to 20 in the system.

4. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The temperature of the in-situ sulfidation reaction in step 1) is 180-360°C, the time is 0-36 h, and the hydrogen pressure is 0-8 MPa.

5. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The metal ionic liquid in step 2) is [N 8881 ]2CoCl4, [N 8881 ]FeCl4, [N 8881 ]2NiCl4, [N 8881 ]2CuCl4, [N 8881 ]2ZnCl4, [N 8881 ]2WO4; its usage is calculated according to the molar ratio of metal atoms in MoS2 carrier of 0~3.

6. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The doping reaction in step 2) is carried out under normal pressure N2 atmosphere, with a reaction temperature of 250-450°C and a reaction time of 0-36 h.

7. The method for preparing a single-atom metal-doped hydrophobic MoS2 catalyst according to claim 1, characterized in that: The reduction in step 2) is carried out in a mixed gas atmosphere of 10% H2 / 90% Ar, the reaction temperature is 150-800°C, and the reaction time is 1-10 h.

8. Use of a single-atom metal-doped hydrophobic MoS2 catalyst prepared by the method as claimed in claim 1 in the hydrodeoxygenation reaction of biomass oil.

9. The use according to claim 8, characterized in that: The biomass oil includes one or more of lignin pyrolysis oil, biomass pyrolysis oil, biomass-based oxygen-containing compounds, and biological oils and fats.

10. The use according to claim 8, characterized in that In the reaction, the mass ratio of the single-atom metal-doped hydrophobic MoS2 catalyst to the biomass oil used is 1-20%, the reaction hydrogen pressure is 0-10 MPa, the reaction temperature is 30-400°C, the reaction time is 0-36 h, and the hydrogen-to-oil ratio is 0-2000.

Citation Information

Patent Citations

  • Catalyst system for advanced metal-air batteries

    CA2970798A1

  • Hydrophobic and lipophilic hydrodeoxygenation catalyst, as well as preparation method and application of catalyst

    CN106964373A

  • Preparation method for nano-scale supported molybdenum sulphide catalyst

    CN109465018A

  • Application and using method of MoS2-ZnO heterostructure serving as reversible light-controlled wetting material

    CN111139478A

  • Preparation method of high-activity molybdenum sulfide hydrogenation catalyst

    CN111229258A